Terfenadine resensitizes doxorubicin activity in drug-resistant ovarian cancer cells via an inhibition of CaMKII/CREB1 mediated ABCB1 expression - Huang, Wei; Yang, Shu; Cheng, Yu-Shan; Sima, Ni; Sun, Wei; Shen, Min; Braisted, John C.; Lu, Weiguo; Zheng, Wei (Frontiers in Oncology, 2022)
Ovarian cancer is one of the most lethal gynecological malignancies. Recurrence or acquired chemoresistance is the leading cause of ovarian cancer therapy failure. Overexpression of ATP-binding cassette subfamily B member 1 (ABCB1), commonly known as P-glycoprotein, correlates closely with multidrug resistance (MDR). However, the mechanism underlying aberrant ABCB1 expression remains unknown. Using a quantitative high-throughput combinational screen, we identified that terfenadine restored doxorubicin sensitivity in an MDR ovarian cancer cell line. In addition, RNA-seq data revealed that the Ca2+-mediated signaling pathway in the MDR cells was abnormally regulated. Moreover, our research demonstrated that terfenadine directly bound to CAMKIID to prevent its autophosphorylation and inhibit the activation of the cAMP-responsive element-binding protein 1 (CREB1)-mediated pathway. Direct inhibition of CAMKII or CREB1 had the same phenotypic effects as terfenadine in the combined treatment, including lower expression of ABCB1 and baculoviral IAP repeat-containing 5 (BIRC5, also known as survivin) and increased doxorubicin-induced apoptosis. In this study, we demonstrate that aberrant regulation of the Ca2+-mediated CAMKIID/CREB1 pathway contributes to ABCB1 over-expression and MDR creation and that CAMKIID and CREB1 are attractive targets for restoring doxorubicin efficacy in ABCB1-mediated MDR ovarian cancer.